Aramid diaphragm for battery with lithium alloy negative electrode and application of aramid diaphragm

By applying an aramid coating liquid on the lithium battery separator to form a coating with high tensile resistance, the problem of insufficient tensile strength of the existing lithium battery separator is solved, and the stability of the lithium battery is significantly improved.

CN119833878AActive Publication Date: 2025-04-15TAIZHOU JICUI FENGFANG NEW MATERIAL TECH CO LTD
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202510044403.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-11
Publication Date
2025-04-15
Estimated Expiration
2045-01-11

AI Technical Summary

Technical Problem

The tensile strength of existing lithium battery separators is low and easy to be damaged, making it difficult to fully improve the stability of lithium battery.

Method used

A battery aramid separator with a lithium alloy negative electrode is used to form a coating by coating an aramid coating liquid on the surface of the base film. The coating consists of aromatic polyester, nanocellulose, reinforcement and filler, and the tensile resistance of the separator is improved through hydrogen bonding and reinforcement.

Benefits of technology

It significantly improves the tensile resistance of the lithium battery separator, reduces the risk of damage of the separator during production, installation and operation, and improves the stability of the lithium battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005237911250000061
    Figure BDA0005237911250000061
  • Figure BDA0005237911250000062
    Figure BDA0005237911250000062
  • Figure BDA0005237911250000071
    Figure BDA0005237911250000071
Patent Text Reader

Abstract

The invention relates to the technical field of lithium batteries, and particularly discloses an aramid diaphragm for a battery with a lithium alloy negative electrode and application of the aramid diaphragm. According to the diaphragm disclosed by the invention, through synergistically associated hydrogen bonds among the components in the coating and a reinforcing effect generated by each component, the overall tensile strength of the diaphragm is remarkably improved, and the defect of insufficient tensile strength of an existing diaphragm is fully overcome. The diaphragm disclosed by the invention is not easy to damage in the production, installation and operation processes of the lithium battery, can be kept stable for a long time, and is beneficial to fully improving the stability of the lithium battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lithium batteries, and more specifically, to an aramid diaphragm for a battery having a lithium alloy negative electrode and its application. Background Art

[0002] Lithium battery is a rechargeable battery. The related concept was first proposed in the United States in the 1950s and entered the practical stage in the 1970s. Lithium battery mainly relies on the movement of lithium ions between the positive and negative electrodes to work. It plays an important role in emerging high-end fields such as electric vehicles, 3C electronic products, and energy storage power stations. With the vigorous development of these fields in recent years, new products have put forward higher requirements for the stability of lithium batteries.

[0003] Traditional lithium batteries use lithium metal as the negative electrode material. During the charging process, lithium ions obtain electrons at the cathode and are reduced to lithium. The lithium produced in this case is prone to form dendrites with a large specific surface area, which not only easily leads to battery short circuit, but also affects the chemical activity of the electrolyte solvent, bringing huge safety hazards to lithium batteries and reducing the stability of lithium batteries. Since the 1960s, scholars at home and abroad have been studying methods to inhibit the growth of dendrites, and lithium alloy negative electrode materials are one of the important research results. Lithium alloy negative electrode materials refer to alloys formed by lithium and elements such as aluminum, boron, silicon, tin, carbon, and bismuth. They can well inhibit the growth of dendrites and improve the stability of lithium batteries. Moreover, according to relevant studies, in PEO polymer gel electrolytes, the cyclic stability of lithium alloys at different current densities is higher than that of metallic lithium. The full battery performance test matched with the LFP positive electrode shows that lithium alloys have electrochemical properties better than pure lithium metal and can solve a series of problems existing in pure lithium metal negative electrodes. In addition, in the PEO gel polymer electrolyte with LLZTO added, the lithium alloy electrode also exhibits excellent electrochemical properties.

[0004] Regarding the above-mentioned related technologies, the inventors believe that although the use of lithium alloy as the negative electrode material can improve the stability of lithium batteries to a certain extent, the tensile strength of current lithium battery separators is generally low, and they are easily damaged during the production, installation, and operation of lithium batteries, resulting in lithium battery failure, making it difficult to fully improve the stability of lithium batteries. Summary of the invention

[0005] In the related art, the tensile strength of lithium battery separators is generally low and easily damaged, which makes it difficult to fully improve the stability of lithium batteries. In order to improve this defect, the present application provides an aramid separator for batteries with a lithium alloy negative electrode and its application.

[0006] In a first aspect, the present application provides an aramid diaphragm for a battery having a lithium alloy negative electrode, which adopts the following technical solution: An aramid diaphragm for a battery with a lithium alloy negative electrode, the diaphragm comprising a base film and a coating, the coating being coated on the surface of the base film, the coating being formed by curing an aramid coating liquid, the aramid coating liquid comprising the following components by weight percentage: 15-20% aromatic polyester, 1.2-1.6% nanocellulose, 3-5% adhesive, 3.2-3.6% reinforcing agent, 4.3-4.5% filler, the remainder being supplemented to 100% by a solvent; the reinforcing agent comprising polyimide, the filler comprising filling powder and modified whiskers, the modified whiskers being inorganic whiskers with copolymer chain segments grafted on the surface, the copolymer chain segments having amino groups.

[0007] By adopting the above technical scheme, the present application uses aramid coating liquid to prepare a coating on the surface of the base film, and adds nanocellulose, reinforcing agent and filler to the aramid coating liquid, and also preferably uses polyimide as a component of the reinforcing agent. Nanocellulose is a green and renewable nanomaterial obtained by hydrolysis of natural cellulose, and has a large number of hydroxyl groups on the surface; the polyimide in the reinforcing agent can be reinforced by the rigidity of the aromatic ring and the imide ring itself, and can also participate in the formation of hydrogen bonds through the nitrogen and oxygen atoms in the imide ring; the modified whiskers in the filler inherit the good mechanical properties of the inorganic whiskers, and can form hydrogen bonds with nanocellulose, polyimide, aromatic polyester and other components through the surface grafted copolymer segments. Through the synergistic hydrogen bonds between the components inside the coating, and the reinforcement effect of each component, the overall tensile strength of the diaphragm is significantly improved, thereby effectively overcoming the defect of insufficient tensile strength of the existing diaphragm. Therefore, the diaphragm of the present application is not easy to be damaged during the production, installation and operation of the lithium battery, and can remain stable for a long time, which is conducive to fully improving the stability of the lithium battery.

[0008] Preferably, the modified whisker is prepared according to the following method: (1) drying the inorganic whiskers, then mixing the inorganic whiskers and a silane coupling agent, adding the mixture to an ethanol aqueous solution, firstly performing ultrasonic dispersion, and then performing oil bath heating to obtain silanized whiskers; in this step, the silane coupling agent includes γ-methacryloxypropyltrimethoxysilane; (2) adding the silanized whiskers and SDS into water for ultrasonic dispersion to obtain a whisker dispersion, adding potassium persulfate aqueous solution and monomers into the whisker dispersion, heating and reacting under nitrogen protection, and demulsifying, filtering and drying after the reaction to obtain modified whiskers; in this step, the monomers include acrylamide.

[0009] By adopting the above technical scheme, the present application first uses a silane coupling agent to treat the inorganic whiskers, introduces carbon-carbon double bonds on the surface of the inorganic whiskers, and then copolymerizes them with monomers under the initiation of potassium persulfate, thereby grafting amino-containing copolymer segments on the surface of the inorganic whiskers to obtain modified whiskers.

[0010] Preferably, in the step (1) of preparing the modified whisker, the inorganic whisker used is one of potassium titanate whisker and mesoporous titanium dioxide whisker.

[0011] By adopting the above technical solution, the present application optimizes the type of inorganic whiskers, and the preparation of modified whiskers can be achieved by using the above two types of whiskers as the matrix material.

[0012] Preferably, in step (2) of preparing the modified whiskers, the monomers used also include fatty acids.

[0013] By adopting the above technical scheme, fatty acids can introduce carboxyl groups into the copolymer chain segments, and the long-chain hydrocarbon structure of the fatty acids themselves provides a larger range of activity for the carboxyl groups, which is conducive to the full formation of hydrogen bonds, so that the tensile strength of the coating can be improved, which helps to fully overcome the defect of insufficient tensile strength of the existing diaphragm.

[0014] Preferably, the fatty acid is oleic acid or linolenic acid.

[0015] By adopting the above technical scheme, compared with oleic acid, linolenic acid has three carbon-carbon double bonds that can participate in polymerization, thereby increasing the number of side chains in the copolymer chain segment, which is beneficial to the full formation of hydrogen bonds, so that the tensile capacity of the coating can be improved, which helps to fully overcome the defect of insufficient tensile strength of the existing diaphragm.

[0016] Preferably, in step (2) of preparing the modified whiskers, the monomers used also include styrene.

[0017] By adopting the above technical scheme, the benzene ring introduced by styrene can make the copolymer chain segments on the surface of the modified whiskers have good compatibility with aromatic polyesters and polyimides, which is beneficial to the uniform dispersion of the modified whiskers and promotes the uniform distribution of hydrogen bonds, thereby improving the tensile strength of the coating and increasing the overall tensile strength of the diaphragm.

[0018] Preferably, in step (2) of preparing the modified whiskers, the monomers used also include polyethylene glycol acrylate.

[0019] By adopting the above technical solution, polyethylene glycol acrylate can introduce polyethylene glycol side chains into the copolymer chain segments after participating in the copolymerization. The polyethylene glycol side chains contain a large number of ether bonds, have good deformability, and are easy to entangle with other chain segments. In addition, the ether bonds can also participate in the formation of hydrogen bonds. In the case of synergistic cooperation with nanocellulose, polyimide, aromatic polyester and other components, the distribution density of hydrogen bonds can be further increased, which helps to improve the overall tensile strength of the diaphragm.

[0020] Preferably, the filling powder comprises carbonized diatomaceous earth, and the carbonized diatomaceous earth is prepared as follows: diatomaceous earth and glucose are added into water and mixed, the mixture is filtered after stirring, the filter residue is dried to constant weight, and then carbonized in a muffle furnace to obtain carbonized diatomaceous earth.

[0021] By adopting the above technical solution, the present application uses glucose as a carbon source to carbonize diatomite. After carbonization modification, the carbonized diatomite surface obtained has a large roughness and carries a large number of silanol groups, which can form a highly complex hydrogen bond cross-linked structure with components such as nanocellulose, polyimide, and aromatic polyester, which helps to improve the overall tensile strength of the diaphragm.

[0022] Preferably, the amount of carbonized diatomaceous earth used accounts for 3-5% of the total weight of the filler.

[0023] By adopting the above technical solution, the present application optimizes the dosage range of carbonized diatomaceous earth, which helps to improve the overall tensile strength of the diaphragm.

[0024] In a second aspect, the present application provides an application of an aramid diaphragm for a battery having a lithium alloy negative electrode, using the following technical solution.

[0025] An application of an aramid diaphragm for a battery with a lithium alloy negative electrode, wherein any of the above-mentioned aramid diaphragms for a battery with a lithium alloy negative electrode is installed in a lithium battery with a lithium alloy negative electrode.

[0026] By adopting the above technical solution, the lithium alloy negative electrode can prevent the generation of lithium dendrites during the operation of the lithium battery, reducing the impact of lithium dendrites on the stability of the lithium battery. The diaphragm has high stability and is not easily damaged during the production, installation and operation of the battery. It can remain stable for a long time, thus fully realizing the improvement of the stability of the lithium battery.

[0027] In summary, this application has the following beneficial effects: 1. The diaphragm of the present application is not easily damaged during the production, installation and operation of lithium batteries and can remain stable for a long time, which is conducive to fully realizing the improvement of lithium battery stability and promoting the development of lithium battery technology.

[0028] 2. In this application, polyethylene glycol acrylate is preferably used as the monomer used in the process of preparing the modified whiskers, which can introduce polyethylene glycol side chains into the copolymer segments. The polyethylene glycol side chains contain a large number of ether bonds, have good deformability, and are easily entangled with other segments. Moreover, the ether bonds can also participate in the formation of hydrogen bonds. When coordinated with components such as nanocellulose, polyimide, and aromatic polyester, the distribution density of hydrogen bonds can be further increased, which helps to improve the tensile strength of the entire diaphragm.

[0029] 3. The present application carbonizes diatomite to obtain carbonized diatomite. The carbonized diatomite has a relatively large surface roughness and carries a large number of silanol groups, which can form a highly complex hydrogen bond cross-linked structure with components such as nanocellulose, polyimide, and aromatic polyester, which helps to improve the overall tensile strength of the diaphragm. DETAILED DESCRIPTION

[0030] The present application is further described in detail below in conjunction with embodiments, preparation examples and comparative examples. The raw materials involved in the present application can all be obtained commercially.

[0031] Preparation example of modified whiskers The following is an explanation using Preparation Example 1.

[0032] Preparation Example 1 In this preparation example, the ethanol aqueous solution is prepared by anhydrous ethanol and deionized water in a volume ratio of 7:3; the inorganic whiskers are potassium titanate whiskers (average diameter of 47 nm, average length of 0.85 μm), the silane coupling agent is γ-methacryloxypropyltrimethoxysilane, and the monomer is acrylamide.

[0033] In this preparation example, the modified whiskers were prepared according to the following method: (1) drying the inorganic whiskers at 110° C., and after 5 hours, mixing 100 g of the inorganic whiskers and 10 g of a silane coupling agent, adding the mixture to 2 L of an ethanol aqueous solution, firstly performing ultrasonic dispersion for 1 hour, and then performing oil bath heating at 100° C. for 3 hours to obtain silanized whiskers; (2) 100 g of silanized whiskers and 1 g of SDS were added to 2 L of water for ultrasonic dispersion to obtain a whisker dispersion, 10 mL of an aqueous potassium persulfate solution containing 0.25 g of potassium persulfate and 25 g of a monomer were added to the whisker dispersion, and the mixture was heated at 80° C. for 6 h under nitrogen protection. After the reaction was completed, the mixture was demulsified, filtered and dried to obtain modified whiskers.

[0034] Preparation Example 2 The difference between this preparation example and preparation example 1 is that the inorganic whiskers used in step (1) are mesoporous titanium dioxide whiskers (average diameter 120 nm, average length 1.2 μm, specific surface area 65 m 2 / g).

[0035] Preparation Example 3 The difference between this preparation example and preparation example 2 is that the monomer used in step (2) also includes fatty acid, the molar ratio of fatty acid to acrylamide is 1:35, and oleic acid is selected as the fatty acid.

[0036] Preparation Example 4 The difference between this preparation example and preparation example 3 is that linolenic acid is used as the fatty acid.

[0037] Preparation Example 5 The difference between this preparation example and preparation example 4 is that the monomer used in step (2) also includes styrene, and the molar ratio of styrene to acrylamide is 1:10.

[0038] Preparation Example 6 The difference between this preparation example and preparation example 5 is that the monomer used in step (2) also includes polyethylene glycol acrylate (average molecular weight 2800).

[0039] Preparation example of carbonized diatomite The following is an explanation using Preparation Example 7.

[0040] Preparation Example 7 In this preparation example, carbonized diatomaceous earth was prepared according to the following method: 50 g of diatomaceous earth with an average particle size of 20 nm and 50 g of glucose were added to 0.5 L of water and mixed, and the mixture was stirred at a rate of 400 rpm for 6 hours and then filtered. The filter residue was dried to constant weight at 70° C. and then carbonized in a muffle furnace at a temperature of 300° C. for 2 hours to obtain carbonized diatomaceous earth. Example

[0041] Examples 1-5 The following description is given by taking Example 1 as an example.

[0042] Example 1 In this embodiment, the aromatic polyester is aromatic polyester (LCPT820) provided by Mitsubishi Engineering-Plastics Corporation of Japan, the reinforcing agent is polyimide (model P84@NT2), the average length of the nanocellulose is 280nm, and the average diameter is 5nm; the filler is a mixture of filling powder and modified whiskers, the amount of filling powder accounts for 2.5% of the total weight of the filler, the filling powder is diatomaceous earth with an average particle size of 20nm, the modified whiskers are prepared according to the method of Preparation Example 1, the adhesive is vinylidene fluoride-trifluoroethylene copolymer, and the solvent is DMF.

[0043] The present embodiment provides an aramid diaphragm for a battery with a lithium alloy negative electrode, including a base film and a coating. The base film is a PET non-woven fabric with a thickness of 25 μm and a porosity of 59%. The coating is coated on the surface of the base film. The coating is formed by curing an aramid coating liquid. The aramid coating liquid includes the following components by weight percentage: 15% aromatic polyester, 1.2-1.6% nanocellulose, 3-5% adhesive, 3.2-3.6% reinforcing agent, 4.3-4.5% filler, and the balance is supplemented to 100% by solvent.

[0044] The aramid separator for the battery with a lithium alloy negative electrode of this embodiment is prepared according to the following method: (1) mixing aromatic polyester, nanocellulose, adhesive, reinforcing agent, filler and solvent to obtain aramid coating liquid for standby use; (2) coating the aramid coating liquid on both sides of the base film at a coating rate of 5 m / min by gravure coating to obtain a coating layer; (3) The coating layer was preheated with water vapor for 15 seconds in an environment with 95% humidity, and then dried with hot air to solidify the coating layer into a coating with a thickness of 7.5 μm, thereby obtaining an aramid separator for a battery with a lithium alloy negative electrode.

[0045] This embodiment provides an application of an aramid diaphragm for a battery having a lithium alloy negative electrode. The aramid diaphragm of this embodiment is installed in a lithium battery having a lithium alloy negative electrode.

[0046] As shown in Table 1, the main difference between Examples 1-5 is that the raw material ratios of the aramid coating liquid are different.

[0047] Table 1 Ratio of raw materials of aramid coating liquid Embodiment 5-10 As shown in Table 2, the difference between Examples 5-10 is that the preparation examples of the modified whiskers are different.

[0048] Table 2 Preparation example of modified whiskers Embodiment 11 The difference between this embodiment and embodiment 10 is that the filling powder is the carbonized diatomaceous earth of preparation example 7.

[0049] Example 12 The difference between this embodiment and embodiment 11 is that the amount of modified diatomaceous earth used accounts for 3% of the total weight of the filler.

[0050] Embodiment 13 The difference between this embodiment and embodiment 11 is that the amount of modified diatomaceous earth used accounts for 4% of the total weight of the filler.

[0051] Embodiment 14 The difference between this embodiment and embodiment 11 is that the amount of modified diatomaceous earth used accounts for 5% of the total weight of the filler.

[0052] Comparative Example Comparative Example 1 The difference between this comparative example and Example 1 is that the components of the aramid coating liquid do not include modified whiskers.

[0053] Comparative Example 2 The difference between this comparative example and Example 1 is that the modified whiskers are replaced by unmodified potassium titanate whiskers.

[0054] Comparative Example 3 The difference between this comparative example and Example 1 is that the components of the aramid coating liquid do not include nanocellulose.

[0055] Comparative Example 4 The difference between this comparative example and Example 1 is that the components of the aramid coating liquid do not include a reinforcing agent.

[0056] Performance testing methods The tensile strength of the diaphragms of the embodiments and comparative examples was tested using a universal tensile machine (Zwick Z100). The sample size selected during the test was 20 mm × 80 mm, and the tensile speed was set to 10 mm / min. After the test, the ratio between the tensile strength of each embodiment and comparative example and the tensile strength of comparative example 1 was calculated based on the tensile strength of comparative example 1, and the ratio was recorded as the relative tensile strength. The results are shown in Table 3.

[0057] Table 3 Relative tensile strength Combining Examples 1-5 and Comparative Examples 1-4 and Table 3, it can be seen that the relative tensile strength measured for the diaphragm of Examples 1-5 is relatively high. This is because the modified whiskers and polyimide of Examples 1-5 have a certain reinforcing effect, and the modified whiskers can form hydrogen bonds with nanocellulose, polyimide, aromatic polyester and other components through the surface-grafted copolymer segments. Therefore, the coating of Examples 1-5 has a high tensile performance, which fully improves the tensile strength of the diaphragm as a whole. In contrast, Comparative Examples 1-4 are difficult to fully realize the synergistic effect between the modified whiskers, nanocellulose, polyimide, aromatic polyester and other components, so the tensile strength of the diaphragm as a whole is not effectively improved.

[0058] Combining Example 5 and Comparative Example 6 with Table 3, it can be seen that the modified whiskers prepared using potassium titanate whiskers and mesoporous titanium dioxide whiskers can both achieve the preparation of modified whiskers, and can improve the tensile strength of the diaphragm by coordinating with other components. Among them, the modified whiskers prepared using mesoporous titanium dioxide whiskers can make a greater contribution to the tensile strength of the diaphragm.

[0059] It can be seen from Example 6 and Examples 7-8 and Table 3 that both oleic acid and linolenic acid can improve the tensile strength of the diaphragm to a certain extent. Among them, linolenic acid can provide more branches, so the relative tensile strength measured in Example 8 is higher.

[0060] It can be seen from Example 8 and Example 9 and Table 3 that the relative tensile strength measured in Example 9 is higher than that in Example 8. This is because the benzene ring introduced by styrene can make the copolymer chain segments on the surface of the modified whiskers have good compatibility with the aromatic polyester and polyimide, which is beneficial to the uniform dispersion of the modified whiskers and promotes the uniform distribution of hydrogen bonds, thereby improving the tensile resistance of the coating and increasing the overall tensile strength of the diaphragm.

[0061] It can be seen from Example 9 and Example 10 and Table 3 that the relative tensile strength measured in Example 10 is higher than that in Example 9, because after the polyethylene glycol acrylate participates in the copolymerization, the polyethylene glycol side chain can be introduced into the copolymer segment. The polyethylene glycol side chain contains a large number of ether bonds, has good deformability, is easy to entangle with other segments, and the ether bonds can also participate in the formation of hydrogen bonds. In the case of coordinated cooperation with components such as nanocellulose, polyimide, and aromatic polyester, the distribution density of hydrogen bonds can be further increased, which helps to improve the tensile strength of the entire diaphragm.

[0062] Combining Example 10, Examples 11-14 and Table 3, it can be seen that the relative tensile strength measured in Examples 11-14 is higher than that in Example 10. This is because after carbonization modification, the carbonized diatomite surface obtained has a greater roughness and carries more silanol groups, which can form a more complex hydrogen bond cross-linked structure with components such as nanocellulose, polyimide, and aromatic polyester, which helps to improve the overall tensile strength of the diaphragm. When the amount of carbonized diatomite accounts for 3-5% of the total weight of the filler, the overall tensile performance of the diaphragm is relatively good.

[0063] The above embodiments are merely explanations of the present application and are not limitations of the present application. After reading this specification, those skilled in the art may make modifications to the embodiments of the present application without any creative contribution as needed. However, as long as they are within the scope of the claims of the present application, they are protected by the patent law.

Claims

1. An aramid separator for a battery having a lithium alloy negative electrode, characterized in that: The diaphragm includes a base film and a coating, wherein the coating is coated on the surface of the base film, and the coating is formed by curing an aramid coating liquid, wherein the aramid coating liquid includes the following components by weight percentage: 15-20% aromatic polyester, 1.2-1.6% nanocellulose, 3-5% adhesive, 3.2-3.6% reinforcing agent, 4.3-4.5% filler, and the remainder is supplemented to 100% by solvent; the reinforcing agent includes polyimide, and the filler includes filling powder and modified whiskers, wherein the modified whiskers are inorganic whiskers with copolymer chain segments grafted on the surface, and the copolymer chain segments have amino groups.

2. The aramid separator for a battery having a lithium alloy negative electrode according to claim 1, characterized in that: The modified whiskers are prepared according to the following method: (1) drying the inorganic whiskers, then mixing the inorganic whiskers and a silane coupling agent and adding them to an ethanol aqueous solution, firstly performing ultrasonic dispersion, and then performing oil bath heating to obtain silanized whiskers; in this step, the silane coupling agent includes γ-methacryloxypropyltrimethoxysilane; (2) adding silanized whiskers and SDS to water for ultrasonic dispersion to obtain a whisker dispersion, adding potassium persulfate aqueous solution and monomer to the whisker dispersion, heating and reacting under nitrogen protection, demulsifying, filtering and drying after the reaction to obtain modified whiskers; in this step, the monomer includes acrylamide.

3. The aramid separator for a battery having a lithium alloy negative electrode according to claim 2, characterized in that: In the step (1) of preparing the modified whisker, the inorganic whisker used is one of potassium titanate whisker and mesoporous titanium dioxide whisker.

4. The aramid separator for a battery having a lithium alloy negative electrode according to claim 2, characterized in that: In the step (2) of preparing the modified whiskers, the monomers used also include fatty acids.

5. The aramid separator for a battery having a lithium alloy negative electrode according to claim 4, characterized in that: The fatty acid is oleic acid or linolenic acid.

6. The aramid separator for a battery having a lithium alloy negative electrode according to claim 2, characterized in that: In the step (2) of preparing the modified whiskers, the monomers used also include styrene.

7. The aramid separator for a battery having a lithium alloy negative electrode according to claim 6, characterized in that: In the step (2) of preparing the modified whiskers, the monomers used also include polyethylene glycol acrylate.

8. The aramid separator for a battery having a lithium alloy negative electrode according to claim 1, characterized in that: The filling powder includes carbonized diatomaceous earth, and the carbonized diatomaceous earth is prepared according to the following method: Diatomaceous earth and glucose are added into water and mixed, and the mixture is filtered after stirring. The filter residue is dried to a constant weight, and then carbonized in a muffle furnace to obtain carbonized diatomaceous earth.

9. The aramid separator for a battery having a lithium alloy negative electrode according to claim 8, characterized in that: The amount of the carbonized diatomaceous earth used accounts for 3-5% of the total weight of the filler.

10. An application of an aramid diaphragm for a battery having a lithium alloy negative electrode, characterized in that: The aramid separator for a battery having a lithium alloy negative electrode as claimed in any one of claims 1 to 9 is installed in a lithium battery having a lithium alloy negative electrode.

Citation Information

Patent Citations

  • Preparation method and application of polyolefin / nanocrystal cellulose composite diaphragm

    CN105185940A

  • Aqueous slurry for lithium battery coating membrane, lithium battery coating membrane and preparation methods of aqueous slurry and lithium battery coating membrane

    CN107611320A

  • Inorganic nanoparticle-modified aramid fiber paste and aramid-coated lithium battery composite diagram

    CN110048063A

  • Preparation method of nano cellulose / aramid fiber lithium battery diaphragm material by heterogeneous process

    CN114865218A

  • Separator for power storage device, and power storage device

    CN115668629A